Long-Term Irrigation Deficits Impair Microbial Diversity and Soil Quality in Arid Maize Fields - Dongdong Zhong; Renhua Sun; Zhen Huo; Jian Chen; Shengtianzi Dong; Hegan Dong (Agronomy, 2025)
Water scarcity in arid regions poses a severe threat to agricultural sustainability, necessitating optimized irrigation strategies. This study investigates the cumulative impacts of long-term irrigation deficits on soil quality, microbial diversity, and maize yield in the arid maize fields of Xinjiang, China, where consistent irrigation patterns have been maintained over multiple years. Seven sites were monitored from April 2023 to March 2024, with a single end-of-cycle sampling in March 2024. Using the Irrigation Water Deficit Index (IWDI), the sites were classified into low (LD, 16.37–22.30%), moderate (MD, 30.54–38.10%), and high drought (HD, 47.49–50.00%) categories. The findings reveal that long-term consistent irrigation deficits exacerbate soil salinization, compaction, and nutrient loss, with organic matter declining significantly under HD conditions. Bacterial richness increased by ~6% under HD, driven by stress-tolerant taxa, while fungal diversity decreased by 14–50%, impairing nutrient cycling functions critical for soil health. The Soil Quality Index (SQI) and maize yield declined with drought severity (LD > MD by 26.18% and 21.05%; LD > HD by 45.02% and 13.13%), highlighting the pivotal role of sustained irrigation patterns in maintaining productivity. These results underscore the need for tailored irrigation management in arid regions, such as precision drip irrigation, to mitigate soil degradation and sustain maize yields, providing a scientific foundation for optimizing water use efficiency in water-scarce agroecosystems under long-term irrigation regimes.